A study on teacher education in India: Physical education, some policy issues and challenges - Ahmed, Mukhtar; Godiyal, Sunita (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
This paper deals with some policies, problems and planned suggestions for teacher education and role of teacher in physical education. The goal of this Special Issue was to raise awareness of physical education teacher education (PETE) by expanding the knowledge base and geographical, theoretical, and innovative writing about PETE, physical education teacher educators, and those who shape (policymakers/higher education leadership) and those who experience PETE. The present research paper is based on explorative types of study. This research study is focused on teachers and physical education in India. This present study is basically case types of study, the researcher used secondary sources. The main implication of the study was to the Govt when any policy is introduced, it is the responsibility to checked in ground level, not only in papers.